Transformasi Perilaku Konsumen dalam Era AI Generatif: Pendekatan Structural Equation Modeling terhadap Pengaruh Konten Cerdas terhadap Persepsi Nilai dan Niat Beli - Halim Dwi Putra; Rashid Ating; April Kim Lalisan; Juwita Azizah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aimed to analyze the transformation of consumer behavior in the era of generative artificial intelligence, particularly focusing on the influence of intelligent content on perceived value and purchase intention. The primary issue addressed was how content generated by artificial intelligence shaped consumers’ cognitive and affective evaluations within an increasingly competitive digital environment. This study employed a quantitative approach using Structural Equation Modeling on data collected from 320 respondents who were users of digital platforms. The findings indicated that intelligent content significantly enhanced consumers’ perceived value, which subsequently exerted a positive effect on purchase intention. Furthermore, perceived value was found to partially mediate the relationship between intelligent content and purchase intention. These results suggested that the utilization of generative artificial intelligence in digital marketing strategies was capable of creating more relevant and personalized experiences, thereby strengthening purchasing decisions. In conclusion, the integration of artificial intelligence technology in content creation represented a key factor in shaping modern consumer behavior.